EFFORTS TO INCREASE STUDENT STUDENTS IN ANALYZING TRANSPORT MECHANISMS ON MEMBRANE CELL THROUGH EXPERIMENTAL METHOD IN XI GRADE OF 1 MALINGPING SENIOR HIGH SCHOOL 2016/2017 - Supandi Supandi (Universitas Sultan Ageng Tirtayasa, 2017)
The students of Class XI IPA D SMA Negeri 1 Malingping difficult to understand On the subject of biology, especially in Class XI IPA D, students' ability is still very low in understanding and analyzing the theories taught in school. Especially in the material transport mechanisms on the cell membrane. In this learning the teacher should multiply the practice activities so that students are able to improve their ability in analyzing the material in teaching. Therefore, previous learning using lecture method will be replaced by using experimental method. The experimental method is a way of teaching in which the student performs an experiment on something, observes the process and writes the results of the experiment, then the results are presented to the class and evaluated by the teacher. The result of this research is pre cycle that still use conventional method in learning number of students who get value above KKM only 13 students, then in cycle 1 researcher start using experiment method in learning process, and result there are 21 student Got a score above the KKM. Continuing on cycle 2, there was another increase of 27 students who scored above the KKM. So in the process and the period is not short, the experimental learning method has a positive impact for students ie students of Class XI IPA D SMA Negeri 1 Malingping can improve its ability in analyzing the mechanism of transport on the cell membrane.